ADRs (Adverse Drug Reactions) related to ayurvedic medicine used in COVID-19 (Bangladesh Journal of Medical Science, 2024)
Background: Adverse Drug Reaction (ADR) is a response to a drug which is noxious and unintended, and which occurs at therapeutic doses. Due to a lack of systematic documentation regarding the occurrence of ADR and other issues to the safety of Ayurvedic medicines, concern about the traditional medical system has recently been increased. This is seen by a rise in safety reports and misunderstandings, especially in the recent pandemic.Objective: To monitor and analyse the suspected ADR to Ayurvedic medicines used in COVID-19.Materials and Methods: ADR monitoring data was collected through spontaneous and intensive method for a span of 2-year (April 2020 to April 2022) during the peak days of COVID-19 from the IPvCC of the National Institute of Ayurveda, Jaipur, India. The IPvCC Program is governed by NPvCC under the supervision of Ministry of AYUSH, Govt. of India, New Delhi. NPvCC is ultimately responsible to monitor and recommend regulatory interventions on the generated national ADR data.Result: In a span of two-year, 142 adverse drug events were reported out of which 17 were confirmed as ADR due to suspected Ayurvedic drugs.Conclusion: Overall review demonstrated that Ayurveda has traditionally been placed a strong emphasis on treatments that aim to heal the underlying illness while preventing the development of new illnesses.Bangladesh Journal of Medical Science Vol. 23 No. 01 January’24 Page : 237-245